Bridging the gap in African biodiversity genomics and bioinformatics - Sharaf, Abdoallah; Ndiribe, Charlotte C.; Omotoriogun, Taiwo Crossby; Abueg, Linelle; Badaoui, Bouabid; Badiane Markey, Fatu J.; Beedessee, Girish; Diouf, Diaga; Duru, Vincent C.; Ebuzome, Chukwuike; Eziuzor, Samuel C.; Jaufeerally Fakim, Yasmina; et al. (Nature biotechnology, 2023)
The Open Institute of the African BioGenome Project empowers African scientists and institutions with the skill sets, capacity and infrastructure to advance scientific knowledge and innovation and drive economic growth.